2008
DOI: 10.1080/10903120802100167
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Emergency Medical Services Use by Children: An Analysis of the National Hospital Ambulatory Medical Care Survey

Abstract: Objective There is an absence of nationally representative data describing pediatric patients who use emergency medical services (EMS) and the factors associated with EMS use by children. This study characterizes pediatric emergency department (ED) visits for which the patient arrived by EMS and identifies factors associated with those visits using a nationally representative database. Methods A secondary analysis of the ED component of the 1997–2000 National Hospital Ambulatory Medical Care Survey was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
135
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 29 publications
(32 reference statements)
11
135
0
1
Order By: Relevance
“…11 Despite these unique needs, Shah et al found that many high-urgency pediatric patients arrive via non-EMS, lacking the specialized judgment of EMS providers. 12 In comparing non-trauma centers and level I-III trauma centers, one study found that 98% of non-trauma center patients are transferred to a higher level trauma center; this study, however, did not distinguish between pediatric and adult trauma patients. 13 A recent analysis of the NHAMCS has shown that within the past 10 years, there has been no change in the percentage of patients using EMS transportation.…”
Section: Introductionmentioning
confidence: 99%
“…11 Despite these unique needs, Shah et al found that many high-urgency pediatric patients arrive via non-EMS, lacking the specialized judgment of EMS providers. 12 In comparing non-trauma centers and level I-III trauma centers, one study found that 98% of non-trauma center patients are transferred to a higher level trauma center; this study, however, did not distinguish between pediatric and adult trauma patients. 13 A recent analysis of the NHAMCS has shown that within the past 10 years, there has been no change in the percentage of patients using EMS transportation.…”
Section: Introductionmentioning
confidence: 99%
“…According to this study, injured children represented more than half (54%), and the most frequently transported time and season were 16:00 p.m. to 23:59 p.m. (47.0%), and in summer (June to August, 31%). 12 Although our study used a different age definition for the pediatric patients (less than 16 years old) than that of the American study, the most common Korean children age group was relatively younger (2 to 5 years old, 31.0%), and prehospital transports were most frequently requested at a relatively earlier time (12:00 p.m. to 17:59 p.m., 36.3%). This discrepancy suggests that national epidemiologic data is essential to establish and to develop specific prehospital transport systems in each country.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] The children transported by EMSS had about a three times higher admission rate than the children brought by other vehicles. 11,12 During the three years of the study, the pediatric proportion of the prehospital transports was 6.5% (n = 238,644). Over time, the proportion slowly but steadily increased, from 6.3% (n = 71,287; in 2006), 6.5% (n = 80,607; in 2007), and 6.6% (n = 86,750; in 2008) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…16 Younger children transported by EMS are more likely to suffer from life-threatening emergencies compared to older children. 1 Younger patients are also the most dissimilar to adults and, in general, may be the pediatric age group at greatest risk for safety events. A previous hospital-based study found that neonates had high rates of potential adverse drug events compared to both adults and other pediatric age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Children account for 4 to 22% of all emergency medical services (EMS) transports, [1][2][3] with infants less than one year of age being among the most common. 4 Children transported by ambulance for emergency care are often higher acuity than those who arrive by other means 1 ; yet, EMS providers have limited experience, 5 pediatric-specific training, 6,7 and resources 3,8 to make critical decisions in caring for sick pediatric patients, creating a low-frequency, high-stakes situation at risk for patient safety events.…”
Section: Introductionmentioning
confidence: 99%